Action Research: Hypnotherapy to Overcome Pain and Anxiety in Colon Cancer Patients - Sakiyan, Sakiyan (Universitas Muhammadiyah Yogyakarta, 2015)
Hypnoterapi action research on pain management and anxiety based colon cancer patients in the problems of pain and anxiety often expressed by colon cancer patients who have undergone surgery and is in the process of chemotherapy, anxiety will increase when individuals face the threat of a life change as a result of disease and duration of the treatment process. The root of the problem in this research is how hypnotherapy reduce pain and anxiety in patients with colon cancer in a surgical disease inpatient unit RSU Banyumas. Design a qualitative research approach action research/action research using Elliot›s Action Research Model, which consists of the process of identifying the initial idea, searching and analyzing facts about pain and anxiety, making planning hypnoterapi, action hypnoterapi, evaluate the success or failure of interventions hypnotherapy, revise ideas, the steps are performed in three cycles. Formulation of the problem in this research is «How to decrease pain and anxiety in patients with colon cancermafter hypnotherapy in the inpatient surgical disease RSU Banyumas». Data processing and data interpretation using NVivo software 9.0.204.0. Based on the data obtained during the application of the three cycles of action showed that hypnotherapy is eff ective in reducing pain and anxiety in patients with colon cancer who are undergoing chemotherapy inpatient unit RSU Banyumas. Decrease in pain every cycle between 4 to 6.3, while the average decrease anxiety between 7 to 15.8. Conclusions in hypnotherapy research helpful in reducing pain and anxiety of patients who suff er from colon cancer and is undergoing chemotherapy in RSU Banyumas. Researchers hope hypnoterapi intervention can be arranged with a standard operating procedure nursing care in the health facilities and can be learned by nurses through nursing education curriculum.Keywords: hypnotherapy, colon cancer, pain, anxiety.